Mesopelagic fishes are important prey for a diversity of predators - Iglesias, Ilysa S.; Santora, Jarrod A.; Fiechter, Jerome; Field, John C. (Frontiers in Marine Science, 2023)
Through daily vertical movements, mesopelagic fishes contribute to global carbon export and when eaten, link primary consumers to higher trophic level predators. Although the importance of mesopelagic fishes as prey to individual predator species has been explored, a comprehensive assessment of mesopelagic fishes as prey at the scale of a large marine ecosystem would advance our observing, modeling, and predicting of biodiversity and ecosystem function. We use diet samples from over 105,000 individual predators from 143 taxa in the California Current Ecosystem (CCE) to quantify and evaluate the role of mesopelagic fishes as prey. For 11 predator taxa, including protected mammal species, pelagic squids, a shelf-edge associated rockfish and highly migratory species, mesopelagic fishes occurred in greater than 25% of all diet samples, likely comprising an important source of prey. Of the 143 taxa represented, individuals from 36 taxa, or 25% percent of all predator taxa in the database, consumed at least 1 mesopelagic fish species, including economically important fishery species such as: Bluefin tuna (16% of all non-empty diet samples), Albacore (19%), Swordfish (50%), Humboldt squid (52%) and Pacific hake (4%). Compared to coastal pelagic fish species (essential prey in the CCE), mesopelagic fish were more frequently encountered in the diets of 21 predator taxa. Lanternfish (family Myctophidae) were the most common prey and consumed by the greatest diversity of predators (32 taxa), but an additional 16 families of mesopelagic fishes were also consumed by predators, highlighting the diversity of organisms inhabiting mesopelagic depths. Mesopelagic fishes were found in the diets of predators collected from shelf depths to well offshore, accentuating the role of mesopelagic fishes as prey across habitats, especially for predators foraging over the slope and further offshore. Our work illuminates the importance of mesopelagic fishes as prey to a diversity of economically valuable and protected species, underscoring the need to incorporate mesopelagic fishes more comprehensively into food web models, global carbon budgets and our ultimately our understanding of ecosystem function.